3
$\begingroup$

Determine all $f : \mathbb R \rightarrow \mathbb R$ that satisfies

$xf(x) - yf(y) = (x-y)f(x+y)$ ; $\forall x , y \in \mathbb R$

I tried reform the equation to

$f(x) + f(-x) = 2f(0)$ and $f(x) + f(3x) = 2f(2x)$. Also, $f$ is injective if $f$ isn’t constant.

Can anyone give me some hints please. Thank you very much!

$\endgroup$
2
  • 4
    $\begingroup$ One observation is that if $f$ has these properties, then so does $f+c$ for any constant $c$. So you can safely assume $f(0)=0$. $\endgroup$ – Qiyu Wen May 17 '20 at 5:43
  • 2
    $\begingroup$ take x = y+1, then try to find derivative of f $\endgroup$ – Sagar Chand May 17 '20 at 5:48
6
$\begingroup$

Write the given functional equation for the three pairs $(x,y)$, $(y,z)$, $(z,x)$, and add up. You then obtain $$0=(x-y)f(x+y)+(y-z)f(y+z)+(z-x)f(z+x)\ .$$ We now have a functional equation with three free variables. Put $$x:={t+1\over2},\quad y:={t-1\over2},\quad z:={1-t\over2}\ ,$$ and you get $$0=1\cdot f(t)+(t-1)\cdot f(0)-t\cdot f(1)\ ,$$ or $$f(t)=f(0)+t\bigl(f(1)-f(0)\bigr)\qquad\forall t\in{\mathbb R}\ .$$ This shows that $f$ has to be of the form $f(t)=at+b$ with arbitrary constants $a$, $b$.

$\endgroup$
2
$\begingroup$

Here are a few hints : use $\frac{xf(x)-(y+z)\bigg(\frac{yf(y)-zf(z)}{y-z}\bigg)}{x-(y+z)}=\frac{(x+y)\bigg(\frac{xf(x)-yf(y)}{x-y}\bigg)-zf(z)}{(x+y)-z}$ to show that $f(z)=\frac{xf(y)-yf(x)+z(f(x)-f(y))}{x-y}$. Deduce that there are two constants $a,b$ such $f(z)=az+b$, then plug into the original equation.

$\endgroup$
2
$\begingroup$

Here's another interesting solution: $$xf(x)−yf(y)=(x−y)f(x+y)\iff x(f(x+y)-f(x))=y(f(x+y)-f(y))$$ Let, $$g(x)=\frac{f(x)-f(0)}{f(1)-f(0)} \iff g(x)(f(1)-f(0))+f(0)=f(x)$$ So, now, $g(1)=1$ and $g(0)=0$ and $$x(g(x+y)-g(x))=y(g(x+y)-g(y))$$ $$y=1 \implies x(g(x+1)-g(x))=g(x+1)-1 \tag{1}$$ $$y=-x \implies-g(x)=g(-x) \tag{since $g(0)=0$}$$ $$y=1-x \implies x(1-g(x))=(1-x)(1-g(1-x))$$ Replacing $x$ with $-x$ in the previous equation yields (knowing the fact that $g$ is odd) $$ -x(1+g(x))=(x+1)(1-g(x+1))\iff 2x+1=x(g(x+1)-g(x))+g(x+1)$$ $$\implies2g(x+1)=2(x+1) \tag{by (1)}$$ $$\implies g(y)=y \ \ \ \ \forall \ y \in \mathbb{R}$$ $$\implies f(x)=ax+b \ \ \ \ \forall \ a,b,x \in \mathbb{R}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.